PENERAPAN DIAGRAM PENGENDALI NONPARAMETRIK EXPONENTIALLY WEIGHTED MOVING AVERAGE SIGN UNTUK ANALISIS PERGERAKAN HARGA SAHAM SEKTOR PROPERTI - Radian Lukman; Mustafid Mustafid; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2023)
Stocks are evidence of equity participation in a company. Investors need to know the quality of stock prices so that they can minimize losses when investing. Technical analysis can be used by investors to decide when to buy or sell a stock. One of the technical analysis that can be used on stock prices is using quality control. Control charts can be used to make decisions in stock trading activities. The Exponentially Weighted Moving Average control chart is very useful for detecting small shifts such as in financial data. The assumption that must be fulfilled in using the EWMA control chart is that the data is normally distributed. The non-fulfillment of the normal distribution assumption causes the EWMA control chart produces plots that are far from the control limits. This problem can be solved using the nonparametric EWMA Sign control chart. The construction of the nonparametric EWMA Sign control chart on stock prices is expected to overcome the limitations of the standard EWMA control chart and provide a signal to investors to know the best time to trade stocks. The data used in this study is the daily closing price data of PT Bumi Serpong Damai Tbk on March 1, 2021 to March 4, 2022 with a total of 250 data. The nonparametric EWMA Sign control chart shows that the daily closing price data is out of control because it produces plots that are spread out non-randomly and shows a relatively similar pattern.